Christian-Muslim relations in Syria - Ashdown, Andrew, 1964- author.
1 online resource (xix, 249 pages).
Keywords: “Offering an authoritative study of the plural religious landscape in modern Syria and of the diverse Christian and Muslim communities that have cohabited the country for centuries, this volume considers a wide range of cultural, religious and political issues that have impacted the interreligious dynamic, putting them in their local and wider context. Combining fieldwork undertaken within government-held areas during the Syrian conflict with critical historical and Christian theological reflection, this research makes a significant contribution to understanding Syria's diverse religious landscape and the multi-layered expressions of Christian-Muslim relations. It discusses the concept of sectarianism and how communal dynamics are crucial to understanding Syrian society. The complex wider issues that underlie the relationship are examined, including the roles of culture and religious leadership; and it questions whether the analytical concept of sectarianism is adequate to describe the complex communal frameworks in the Middle Eastern context. Finally, the study examines the contributions of contemporary Eastern Christian leaders to interreligious discourse, concluding that the theology and spirituality of Eastern Christianity, inhabiting the same cultural environment as Islam, is uniquely placed to play a major role in interreligious dialogue and in peace-making. The book offers an original contribution to knowledge and understanding of the changing Christian-Muslim dynamic in Syria and the region. It should be a key resource to students, scholars and readers interested in religion, current affairs and the Middle East“--